INDOCTRINATION: THE PSYCHO-PATHOLOGY OF INTERNATIONAL TERRORISM AND INSURGENCY (THE 5TH GENERATION WARS) - Ezeonwuka, Innocent-Franklyn (Practicum Psychologia, 2018)
Nations, States, Regions, groups and individuals have made insurgency and terrorism not only a global brand, but a necessary corollary of human existence through diverse actions and in-actions. Western depredations, covertly and overtly have continued to globally breed and hatch disillusionment and frustration. Conventional dissent has continued to attract overwhelming decapitation and annihilation of populations through guided policies and military armadas. Organized oppositional resurgence and effective tenacity found unity, determination, blind faith, formation, cohesion and feet in indoctrination; whereby both entrenched regimes could be overthrown and dominant world powers put on the defensive. Before 1979, suicidal methods for voicing dissent were rare, while revolutionary, military and guerrilla-based armed groups had designated state actors to contend with. The aim of this study is not to denigrate indoctrination as a new tool, rather an in-depth move is made to unveil the rewarding tactics whereby it has helped Islamic fundamentalism and extremism to clandestinely stand tall and enjoy global recognition. As long as domination remains a natural human quest, as long as syncretists are out to exploit human frailties and thought patterns, as long as national governments continue to overlook people-oriented policies, global interconnectedness would always provide an alternative assemblage that evolve to threaten national and international security. The dire need to scrutinize and evaluate religious and social ideas impacted to the populace is not in doubt.